2009
DOI: 10.1007/s12011-009-8403-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Gallium on Prevention of Fatal Cage-Layer Osteoporosis

Abstract: The prevention of fatal cage-layer osteoporosis of gallium was studied in this paper. One-day-old hens were fed up to 68 weeks on a control diet and diets containing gallium. Plasma variables were measured during lay. End-of-lay trabecular and medullary bone volumes in the proximal tarsometatarsus and free thoracic vertebra were measured by histomorphometry. Medullary and trabecular bone volumes were increased significantly by supplementation with gallium. The experiment confirmed that dietary gallium suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Gallium readily adsorbs to hydroxyapatite, and it is rapidly incorporated into osteogenic foci [20] and within cells in metabolically active tissues [21]. Chen X reported that dietary gallium supplementation was an effective way to improve cage layer osteoporosis [15]. The present study was carried out to investigate the possible biochemical mechanism of gallium in preventing osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallium readily adsorbs to hydroxyapatite, and it is rapidly incorporated into osteogenic foci [20] and within cells in metabolically active tissues [21]. Chen X reported that dietary gallium supplementation was an effective way to improve cage layer osteoporosis [15]. The present study was carried out to investigate the possible biochemical mechanism of gallium in preventing osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary evidence suggests that dietary gallium supplementation was an effective way to enhance the egg production and reduce mortality percentage. The beneficial effects of gallium supplementation over the lifetime of the hens were attributable mainly to improve cage layer osteoporosis [15].…”
mentioning
confidence: 99%
“…Gallium is a group IIIA metal and was first identified in 1875 by Paul-Émile Lecoq de Boisbaudran in France ( 2 ). Gallium has been demonstrated to be efficacious in the treatment of a number of diverse disorders that are characterized by accelerated bone loss, including cancer-associated hypercalcemia, bone metastases, Paget's disease, myeloma and fatal cage-layer osteoporosis ( 2 9 ). However, the adverse effects associated with gallium limits its use therapeutically for the treatment of osteoporosis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%